Medications for attention‐deficit/hyperactivity disorder in Japan: A retrospective cohort study of label compliance - Daniel Fife; Erica A. Voss; Jill Hardin; Hany Rofael; Ira D. Solomon; Patrick B. Ryan; Paul Stang (Wiley, 2021)
Abstract Aim To assess label compliance in prescription of medications approved for treatment of attention‐deficit/hyperactivity disorder (ADHD) in Japan at the time of this study: methylphenidate (MPH), atomoxetine, and guanfacine. Methods Retrospective descriptive study was conducted in prevalent‐user cohorts from the Japan Medical Data Center database. Patients who were prescribed a study drug between January 1, 2013 and September 30, 2018 and were in the database for ≥30 days were included. A prescription was considered compliant if all 4 criteria were satisfied: appropriate age, daily dose not exceeding the approved maximum, no contraindicated concurrent medications, and no contraindicated conditions. Results Among 17 418 patients who were prescribed a study drug during 2013‐2018, 73% were male and 53% were children (aged <18 years). Fewer than 2% of prescriptions were for patients outside the approved age, 10%‐13% of patients in the atomoxetine and MPH cohorts received ≥1 prescription exceeding maximum approved dose, no patients were co‐prescribed a contraindicated medication, and 16%-18% of patients in the MPH cohorts had ≥1 contraindicated condition. During their first 500 days of use, for approximately 73%‐86% of patients, all prescriptions were compliant with all label requirements. Conclusions Among patients exposed to ADHD medications in Japan during 2013‐2018, nearly all prescriptions for these medications were label‐compliant for age. For >85% of patients, all prescriptions were label‐compliant for dose, and for approximately 80%, all prescriptions were label‐compliant for contraindicated conditions. We did not find evidence of widespread abuse or noncompliant use of prescribed ADHD medications.